The Capital Gains Tax: A Curse but Also a Blessing for Venture Capital Investment3. (20th November 2017) - Bock, Carolin; Watzinger, Martin
Abstract : Our study analyzes the effect of the capital gains tax on the individual investment decisions of venture capitalists. By doing so, we are able to study the decisions for a sample of 61, 558 funding rounds in 32 countries from 2000 to 2012. Our results support the predictions of the theoretical model that higher capital gains tax rates are associated with fewer start‐ups financed and a lower probability of receiving follow‐up funding. However, the results concerning the effect on the probability of success of start‐ups show that a higher tax burden is associated with a higher probability of eventual start‐up success.